ANALYSIS OF MARKETING STRATEGIES IN SUSTAINING MSMEs BUSINESS IN THE MIDDLE OF THE COVID-19 PANDEMIC - Siti Mariam; Retno Wulansari; Pramudi Harsono; Fatari Fatari (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the marketing strategy in MSMEs, especially the applied marketing mix. This study uses a qualitative method: a case study that produces descriptive data described in words. The data source of this study used design sampling techniques and data collection techniques. The authors conducted personal interviews with the MSME Bhayangkara Florist during this study. It includes sales data for several years of return and concluded several discussions, including strategies, constraints, and solutions. The strategy used is the 4P mix (Product, Promotion, Price, and Place). The product strategy is in the form of a bouquet of masks innovation. The promotion strategy is in the form of price discounts. The price strategy is that every bouquet purchase gets a bonus mask. The place strategy is in the form of flexibility in product delivery to maintain and improve product quality. Even though there are financial and raw material constraints, they can still find solutions and alternatives, including managing finances and effectively using natural materials. Then, the MSME's answer in dealing with Covid-19 is to maintain cash flow, product innovation, optimize social media and optimize delivery services